Integrasi Strategi People Development dan Marketing Excellence Studi Holistik Pengelolaan Human Capital di PT. Yakult Indonesia Persada - Cantik Padmasari; Ilham Satya Hermawan; Nadya Nova Mariska; Makinatul Fitriyah; Adji Seputro (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to analyze the integration of People Development and Marketing Excellence strategies in human capital management at PT. Yakult Indonesia Persada. The research applied a qualitative method through observation, interviews, and focus group discussions. Findings reveal that structured HR development, comprehensive training, and personalized marketing strategies via Yakult Lady create synergy that enhances customer loyalty, employee productivity, and corporate image. However, the company faces challenges such as intense competition, shifting consumer behavior among younger generations, and the need for digital transformation. The study recommends HR digitalization, diversified digital marketing, and career development for Yakult Lady to ensure long-term competitiveness.